2011
DOI: 10.1108/15253831111190199
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization of new ventures: tests of growth and survival

Abstract: PurposeThe purpose of this paper is to investigate key contingencies affecting the internationalization of young ventures, and to shed light on early internationalization's implications for organizational survival and growth.Design/methodology/approachA previously suggested conceptual framework is tested based on a quantitative study of UK firms before explorative analysis takes the analysis further.FindingsContrary to the model suggested by Sapienza et al. that internationalization is of increasing importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 105 publications
(141 reference statements)
1
22
1
Order By: Relevance
“…These results are consistent with earlier studies (Coucke and Sleuwaegen 2008;Pla-Barber and Puig 2009). The lack of significance of the moderating effect of age on the internationalisation-survival relationship is in part agreement with results reported by Westhead et al (2001), Zou et al (2010), and Schueffel et al (2011). This implies that in the short and medium term (in our case during the 10 first years), age has only a very weak impact on the internationalisation-survival relationship.…”
Section: Variable Int (And Hence Is Not Included Insupporting
confidence: 91%
See 3 more Smart Citations
“…These results are consistent with earlier studies (Coucke and Sleuwaegen 2008;Pla-Barber and Puig 2009). The lack of significance of the moderating effect of age on the internationalisation-survival relationship is in part agreement with results reported by Westhead et al (2001), Zou et al (2010), and Schueffel et al (2011). This implies that in the short and medium term (in our case during the 10 first years), age has only a very weak impact on the internationalisation-survival relationship.…”
Section: Variable Int (And Hence Is Not Included Insupporting
confidence: 91%
“…Carr et al (2010) found that the age of a firm positively impacts higher survival rates in international markets and that among surviving internationalised ventures, younger firms show higher short-term growth rates than their older counterparts. Schueffel et al (2011) suggested similar relationships in terms of the moderating effect of firm age on survival and growth when entering international markets. Bausch and Krist (2007) found that firm age has a strong impact on the proportion of performance variance that can be attributed to internationalisation.…”
Section: Effect Of Age On the Internationalisation-survival Relationshipmentioning
confidence: 71%
See 2 more Smart Citations
“…The basic argument is that, when expanding internationally, firms are able to develop and adopt new routines once they have unlearned established routines (Barkema and Vermeulen 1998). Such unlearning process becomes increasingly difficult over time since inertial constraints hinder the exploration of opportunities and the development of new routines (Zahra 2005;Schueffel et al 2011;Zhou and Wu 2014). Lock-in mechanisms prevent older firms from learning and developing new competencies and routines.…”
Section: The Positive Effect Of Global Orientationmentioning
confidence: 99%